The Use of Personal Digital Assistants and Smartphones to Access Health Information - Shahram Sedghi; Iman Tahamtan (Tehran University of Medical Sciences, 2012)
Background and Aim: Today, one of the challenges of doctors is how they can access medical information as quick as possible. Personal Digital Assistants (PDAs) and Smartphones are such information technologies that can be used to access health information. This study aimed to review the most important uses of Personal Digital Assistants and Smartphones in medicine and in accessing health information. Materials and Methods: The researchers searched Pubmed, Google Scholar and Scopus to collect relevant articles about the use of PDAs and Smartphones among healthcare professionals. In this search, such terms as Handheld Computer, Smartphone, Personal Digital Assistant, Mobile phone and their synonyms were considered. Conclusion: With regard to the vast amount of information produced daily, PDAs and Smartphones are useful devices for physicians and medical students because they can easily get the most recent bits of information at the point of care, and improve their medical knowledge through these devices. Utilization of PDAs and Smartphones in Medical Centers will improve the efficiency and quality of health services.